(938) Allocation of Space Resources to Social Projects تخصيص الموارد المكانية للمشروعات الاجتماعية - Wafik Ashraf Hassouna. (معهد التخطيط القومى, 2024)
This study examines the impact of school health services on students' health status and its effect on their scholastic achievement. It starts with an introduction and problem statement, followed by a case study on the expenditures in school health services. The research focuses on a model that links health status with academic performance. The study concludes by emphasizing the importance of health status in improving academic outcomes..